In vivo quantitative proton MRSI study of brain development from childhood to adolescence - Horská, Alena; Kaufmann, Walter E.; Brant, Larry J.; Naidu, Sakkubai; Harris, James C.; Barker, Peter B. (Journal of magnetic resonance imaging, 2002)
Purpose To quantify regional variations in metabolite levels in the developing brain using quantitative proton MR spectroscopic imaging (MRSI). Materials and Methods Fifteen healthy subjects three to 19 years old were examined by in vivo multislice proton MRSI. Concentrations of N‐acetyl aspartate (NAA), total choline (Cho), total creatine (Cr), and peak area ratios were determined in selected frontal and parietal gray and white matter regions, basal ganglia, and thalamus. Results In cortical gray matter regions, the ratio of NAA/Cho increased to a maximum at 10 years and decreased thereafter (P = 0.010). In contrast, in white matter, average ratios NAA/Cho increased linearly with age (P = 0.045). In individual brain regions, age‐related changes in NAA/Cho were found in the putamen (P = 0.044). No significant age‐related changes in NAA, Cho, Cr, or other metabolite ratios could be determined. Conclusion Consistent with recent studies using other structural and functional neuroimaging techniques, our data suggest that small but significant changes occur in regional cerebral metabolism during childhood and adolescence. Non‐linear age related changes of NAA/Cho in frontal and parietal areas, resembling previously reported age related changes in rates of glucose utilization and cortical volumes, may be associated with dendritic and synaptic development and regression. Linear age‐related changes of NAA/Cho in white matter are also in agreement with age‐related increases in white matter volumes, and may reflect progressive increases in axonal diameter and myelination. J. Magn. Reson. Imaging 2002;15:137–143. Published 2002 Wiley‐Liss, Inc.